ANALISIS KEGIATAN FORUM MGMP BAHASA ARAB DALAM PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU BAHASA ARAB DI JAWA TENGAH - Rizal Nur Rochman; Maman Abdurrahman; Mad Ali (Universitas Negeri Semarang, 2022)
Abstract: This study aims to identify and describe the management, activities and strategies of the Arabic Language MGMP Forum in developing the pedagogic competence of Arabic teachers in Central Java. The method used in this research is a qualitative approach. Data collection techniques include interviews, questionnaires and documentation studies. Interviews were conducted with the committee, while the questionnaire was given to members of the Central Java Arabic Language MGMP Forum. The results showed that the Central Java Arabic MGMP Forum was optimal in developing the pedagogic competence of Arabic teachers in Central Java. This is evidenced by some programs that adapt to the needs of teachers, but from a management perspective it needs to be improved so that it can run optimally. First, there is a need for management of the Arabic Language MGMP Forum in each city or district in Central Java. Second, there is a need for regular meetings of the core board of the Central Java Arabic MGMP Forum and City/Regency level administrators on a regular basis either offline or online. Third, there needs to be a socialization of the programs of the Central Java Arabic MGMP Forum to Arabic language teachers in Central Java, so that the enthusiasm of members is higher. Fourth, the Central Java Arabic MGMP Forum must increase collaboration with external organizations to jointly support and develop teachers’ pedagogy through the MGMP Forum, collaboration can be done with universities, language centers, and education policy makers from the Ministry of Education and Culture and/or the Ministry of Religion at the provincial level as well as the provincial government or district/city governments in Central Java.